THE DEVELOPMENT CONCEPT OF THERAPY DANCE MODEL AS AN EFFORT TO INCREASE THE INTEREST OF SURYA KIRANA STUDENTS - Nursilah; Sarajar, Michelle Marieta; Putri Najla Ayu Rasyid; Monik Alvianisa; Sihombing, Lusia Dame Mariana (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
Dance that is known by the general public is a dance that functions as a traditional ceremony, entertainment or performance. But on the one hand, dance is able to become a medium for expressing feelings, processing feelings and providing concentration. By using Margareth H. Doubler's method of movement quality, the therapeutic dance model was developed based on existing therapeutic dance theories. The results also showed that there were changes felt to students who underwent therapeutic dance for four meetings as evidenced by the results of observations and interviews conducted together with students.